2(2x+1)=-38

Simple and best practice solution for 2(2x+1)=-38 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2x+1)=-38 equation:


Simplifying
2(2x + 1) = -38

Reorder the terms:
2(1 + 2x) = -38
(1 * 2 + 2x * 2) = -38
(2 + 4x) = -38

Solving
2 + 4x = -38

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2' to each side of the equation.
2 + -2 + 4x = -38 + -2

Combine like terms: 2 + -2 = 0
0 + 4x = -38 + -2
4x = -38 + -2

Combine like terms: -38 + -2 = -40
4x = -40

Divide each side by '4'.
x = -10

Simplifying
x = -10

See similar equations:

| 92-4x=32x+16 | | 6-7x=9x+15 | | 6x+7=1+5x | | 4x-13=5(2x+1) | | 10x+12=76+x | | 2x^3+3x^2-12x-15=y | | Y=100+0.66(Y-200)+250+200+150 | | 3x+47=6x+15 | | Y=100+0.6(Y-200)+250+200+150 | | Y=400+0.5(Y-200)+250+200+150 | | Y=100+0.5(Y-200)+250+200+150 | | 7+ln(27x)=22-2ln(x) | | y(y-6)-6(y-6)= | | 5(x-2)-3(x-1)=0 | | a(a-4)-4(a-4)= | | c(c-5)-5(c-5)= | | m(m-2)-2(m-2)= | | p=(a+b)*2 | | t(t+4)+4(t+4)= | | y(y+2)+2(y+2)= | | Y=150+0.7(Y-200)+50+0.2+200 | | b(b+7)-7(b+7)= | | r(r+4)-4(r+4)= | | p(p-2)+4(p-2)= | | x-4540=40 | | Y=150+0.7(Y-200)+50+0.2Y+200 | | x(x+2)+3(x+2)= | | -7(x-3)=63 | | 342+x=442 | | 8(2+z)-5(3-2z)= | | 2-3x=5x-2(x+8) | | 3(4-5a)-2(5-4a)= |

Equations solver categories